DERADIKALISASI AGAMA MELALUI PENDEKATAN DA’I HIJRAH - Rohmat Suprapto; Yesika Maya Ocktarani (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Lately religious life in Indonesia experienced a fairly loud dynamics with the emergence of many cases of religious radicalism background. This has resulted in loss of lives wasted and physical damage to the building. But more horrible is the breakdown of social relations between the nation and the erosion of social capital of trust  between one another. Though the government has taken various measures such as the establishment of BNPT, Detachment 88 anti-terror legislation and government regulation on the prohibition of blasphemy / desecration of religion. However, this step does not reduce the percentage of religious radicalism. Even more days of religious radicalism increasingly fertile. Pesantren Imam Syuhodo Sukoharjo Central Java have developed and internalized models of religiouseducation curriculum-based multicultural inclusivism in order to counteract the movement of religious radicalism. The curriculum is a set of values that are as straight as implemented by students, such as living together, understand each other differentness, diversity of teaching. The students are taught to live in peace, side by side with each other, in the middle of the variance differences exist between them. In addition, the value Uswah Khasanah (good role models) from Kyai and the Ustadz/Theacer  of the main pillars in the internalization efforts multicultural-inclusivism values in Ponpes Imam Syuhodo Sukoharjo. Keywords : Deradicalised of Religion, Pesantren,